Improving Students Understanding in Listening Lessons with The Use of Film Media - Chairuddin Chairuddin; Muhammad Hasyimsyah Batubara; Dina Wulansari (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
This research is about using English-language film media to facilitate listening lessons. With this film media, it is expected that learners will be more enthusiastic about studying English and pay more attention to correct pronunciation. The research method played in this paper is a quantitative descriptive method. It is done by studying article references related to the analysis of the use of film to improve students' listening comprehension in listening lessons and the data collection by utilizing article references published in OJS-based journals. The research results prove that many studies states that film media can improve students' listening skills. Based on the findings of previous researchers, it can be concluded that the use of film in listening lessons is very appropriate to apply. The use of film makes students like and enjoy listening to lessons more. So it has a significant impact on these students. When students start to like listening lessons using the film method, these students will be more diligent and enthusiastic in listening lessons.